Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Higher Order Thinking Skill (HOTS) Praktikum Akuntansi Lembaga - Sarasasih Wahyuning Mustika; Susanti Susanti (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang)
Implementation of the 2013 Revised 2018 Curriculum at the Vocational High School (SMK) have a various challenges, one of them is the relevant teaching materials available are still not integrated with HOTS. The research was a solution for that problem by arranging the teaching materials as Student Work Sheets (LKPD) HOTS-based. The research design used is the 4D development model by Thiagarajan dkk and modified by researchers without the disseminate stage. So researchers only create products to determine the appropriateness without testing the effectiveness for the students. The research instrument used was a study sheet and an expert validation sheet. The results showed that LKPD based on HOTS in Institutional Accounting Practicum is have appropiate criteria of material, language and graphics, each getting a percentage of 83.57%, 93.85%, and 96.43%. Based on these data, it has an average of 91.28% with categories very decent and suitable for the next research.DOI: https://dx.doi.org/10.17977/UM014v13i22020p125